2018
DOI: 10.1007/s10815-018-1278-2
|View full text |Cite
|
Sign up to set email alerts
|

Pre-implantation genetic testing: decisional factors to accept or decline among in vitro fertilization patients

Abstract: There is a need to develop decision support tools for the increasing choices of genetic testing options for patients seeking IVF. Including patients' values, past pregnancy experiences and attitudes toward science into the decision-making process may help promote a more informed decision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 25 publications
0
43
0
Order By: Relevance
“…Of the 25 full text publications that were examined, 10 met the inclusion criteria. 14,25,26,[32][33][34][35][36][37][38] Of the 15 studies that were excluded, one text was not available in English, two were duplicate studies and 12 were review or opinion…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 25 full text publications that were examined, 10 met the inclusion criteria. 14,25,26,[32][33][34][35][36][37][38] Of the 15 studies that were excluded, one text was not available in English, two were duplicate studies and 12 were review or opinion…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%
“…To collect the data, five of the studies used questionnaires, 25,[32][33][34][35] three studies used an existing database [36][37][38] and two used semi-structured interviews. 14,26 Three of the studies collected data prior to treatment and seven collected their data retrospectively. The sample size range was 21-1500 patients.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in one study, PGT‐A did not improve the live birth rate or reduce the miscarriage rate in RPL patients . Semi‐structured telephone interviews conducted in the USA showed that all patients who were offered PGT‐A expressed the need to become parents . Quinn et al .…”
Section: Discussionmentioning
confidence: 99%
“…No correlation was found between the number of repeats in the premutation carriers and the number of oocytes retrieved, oestradiol levels or fertilization rate. (Lamb et al, 2018), 37 out of 175 (21%) pregnant women at high risk of passing on a FMR1 full mutation in Israel opted for IVF with PGT-M. The key predictors for selecting IVF with PGT-M were previous termination for an affected fetus and an advanced maternal age, whereas women with a history of IVF failure were more likely to choose to conceive naturally and to use prenatal genetic diagnosis testing (Lamb et al, 2018).…”
Section: Discussionmentioning
confidence: 99%